PENERAPAN PEMBIAYAAN MURABAHAH DALAM MENDUKUNG INKLUSI KEUANGAN SYARIAH: STUDI PADA PT BANK SYARIAH INDONESIA (BSI) - Dinda Nur Putri; Indah Alfiyah; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
Indonesia faces big challenges in developing the sharia economy, especially because the level of sharia financial literacy and inclusion is still low. The results of research conducted by the OJK show that the level of sharia financial literacy and inclusion, with the results of a sharia financial literacy index of 39.11 percent and sharia financial inclusion of 12.88 percent. The research method used in this research is descriptive qualitative to understand the murabahah financing policy in supporting Sharia financial inclusion from several previous studies and examine it according to Islamic law so as to obtain data that is structured descriptively. This research is library research or literature research, namely collecting or compiling secondary data obtained from books and previous research journals from Google Scholar. Murabahah financing has an important role in increasing sharia financial inclusion. For those who are not served by the conventional financial system, murabahah financing offers an alternative with a transparent buying and selling concept. This has a good impact on UMKM, which often have difficulty obtaining financing.